Dampak Pupuk Organik Cair dan Kompos IPAL Karet Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq) di Main Nursery - Anis Tatik Maryani; Rada Febriyasti; Sosiawan Nusifera (Universitas Batanghari Jambi, 2023)
Oil palm plants (Elaeis guineensis Jacq) are one of the important commodities in the plantation crop industry, capable of providing economic value as a source of foreign exchange income for the country. The increase in oil palm area is also accompanied by an increase in damaged plants (TR/TTM). So it is necessary to rejuvenate the plants to get quality seeds. The aim of this research was to determine the effect and best dose of Eco Farming liquid organic fertilizer treatment with rubber wastewater treatment plant sludge compost on the growth of oil palm (Elaeis guineensis Jacq.) seedlings in the main nursery. This research was carried out at the Teaching and Research Farm, Faculty of Agriculture, Jambi University and lasted for 3 months, starting in September-November 2022. This research used a Completely Randomized Design (CRD) with 5 treatments, namely: k0 = 40 mL.L-1 Eco fertilizer water Farming, k1 = 30 mL.L-1 Eco Farming fertilizer water + 100 g compost from waste sludge from WWTP, k2 = 20 mL.L-1 water from Eco Farming fertilizer + 200 g compost from waste sludge from WWTP, k3 = 10 mL.L-1 Eco Farming fertilizer water + 300 g of WWTP sludge waste compost, k4 = 400 g of WWTP sludge waste compost. The variables observed included seed height (cm), increase in tuber diameter (mm), increase in number of leaves (strands), shoot dry weight (g), root dry weight (g), ratio of root shoot and root volume (ml). The results of the research showed that the application of Eco Farming liquid organic fertilizer and waste compost from rubber wastewater treatment plant sludge was able to increase growth in the variables of seed height, root dry weight and root volume. However, it has not been able to increase the increase in tuber diameter, increase in number of leaves, shoot dry weight and root shoot ratio. Treatment of 10 mL.L-1 of Eco Farming fertilizer water + 300 g of IPAL waste sludge compost gave the best average growth of 6 month old oil palm seedlings in the main nursery.